Yield evaluation of oyster mushroom on dust waste of some common timber species - Tomy, Minnu; Sneha, C (Mushroom Research, 2019)
An investigation on the feasibility of utilizing sawdust of locally available timber species as potential substrates for cultivation of oyster mushrooms was carried out at the Department of Forestry, Sir Syed College, Kerala during 2013-14. Oyster mushroom (Pleurotus spp.) was selected for the study, because it is the most suitable species for utilization lignocellulosic wastes. Its conversion rate i.e., mushroom production from the substrate is highest and the rate of growth is very fast. Sawdust of most commonly available five timber species were used as substrates which include Swietenia macrophylla, Tectona grandis, Xylia xylocarpa, Terminalia bellirica and Melicope lunu-ankenda. A control treatment was maintained using mixture of saw dust of all these five species in equal proportions. All these six substrates were well sterilized, spawn were inoculated and allowed to incubate under suitable temperature and relative humidity. Mycelial growth and pin head formation was fastest in Xylia and slowest in Terminalia. In Melicope no pin head formation occurred even though there was good mycelia growth. Mushroom yield was maximum in control and minimum in Melicope.